Lipopolysaccharide Pretreatment Prevents Medullary Vascular Congestion following Renal Ischemia by Limiting Early Reperfusion of the Medullary Circulation. Issue 4 (April 2022) - McLarnon, Sarah R.; Wilson, Katie; Patel, Bansari; Sun, Jingping; Sartain, Christina L.; Mejias, Christopher D.; Musall, Jacqueline B.; Sullivan, Jennifer C.; Wei, Qingqing; Chen, Jian-Kang; Hyndman, Kelly A.; Marshall, Brendan; et al.
Significance Statement: The pathogenesis of medullary vascular congestion—red blood cell (RBC) aggregation in the renal medulla vasculature—after renal ischemia has been uncertain. In a rat model, the authors found that during ischemia, sludging of RBCs occurs in the renal venous vasculature. Because recovery of cortical perfusion is required to displace this stalled blood in the shared venous vessels—which drain both the cortex and medulla—restoration of blood flow to the medulla before restoration to the cortex results in tightly packed RBC congestion of the medullary circulation. This congestion then prevents later reperfusion of the medulla, even after blood flow is restored to the cortex, resulting in tubular injury. These findings support a hemodynamic explanation for the susceptibility of the renal medulla to ischemic injury. Visual Abstract: Abstract : Background: Vascular congestion of the renal medulla—trapped red blood cells in the medullary microvasculature—is a hallmark finding at autopsy in patients with ischemic acute tubular necrosis. Despite this, the pathogenesis of vascular congestion is not well defined. Methods: In this study, to investigate the pathogenesis of vascular congestion and its role in promoting renal injury, we assessed renal vascular congestion and tubular injury after ischemia reperfusion in rats pretreated with low-dose LPS or saline (control). We used laser Doppler flowmetry to determine whether pretreatment with low-dose LPS prevented vascular congestion by altering renal hemodynamics during reperfusion. Results: We found that vascular congestion originated during the ischemic period in the renal venous circulation. In control animals, the return of blood flow was followed by the development of congestion in the capillary plexus of the outer medulla and severe tubular injury early in reperfusion. Laser Doppler flowmetry indicated that blood flow returned rapidly to the medulla, several minutes before recovery of full cortical perfusion. In contrast, LPS pretreatment prevented both the formation of medullary congestion and its associated tubular injury. Laser Doppler flowmetry in LPS-pretreated rats suggested that limiting early reperfusion of the medulla facilitated this protective effect, because it allowed cortical perfusion to recover and clear congestion from the large cortical veins, which also drain the medulla. Conclusions: Blockage of the renal venous vessels and a mismatch in the timing of cortical and medullary reperfusion results in congestion of the outer medulla's capillary plexus and promotes early tubular injury after renal ischemia. These findings indicate that hemodynamics during reperfusion contribute to the renal medulla's susceptibility to ischemic injury.